Neutral press, negative opinions: development cooperation and the Dutch media. Issue 6 (17th August 2020) - Vossen, Mirjam
ABSTRACT: Recent high-profile scandals raise concerns about how development cooperation is represented. This article examines how the subject gets in the media, examining the tone of voice and framing in newspaper articles and NGO advertisements in the Netherlands. It reveals a remarkable difference between newspaper articles and opinion pieces. Regular reports are characterised by, a neutral to slightly positive tone. In contrast, opinion pieces are predominantly negative. The article identifies possible explanations for the critical tone of opinion pieces. It finds that NGOs' own advertisements may contribute to negative opinion pieces, by problematising the situation in developing countries while rarely demonstrating their impacts achieved.